WOMEN'S STRUGGLE IN EVITA MOVIE DIRECTED BY ALLAN PARKER:A LIBERAL FEMINIST APPROACH - DEWI, LULUK QIRANA (2010)
The major problem of this study is how struggle in Evita Peron is reflected in Evita movie based on liberal feminist approach. This study is to analyze structural elements of Evita movie and Evita Peron's struggle to reach equal position in public based on liberal feminist point of view This research paper is qualitative research. The object of the study is Evita movie directed by Allan Parker published by Cinergi Pictures Entertainment in 2002. The primary data source is the Evita movie and the secondary data sources are the other sources related to the analysis. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. The result of the study is to show the relationship between the movie and the social phenomena in Argentina around World War II. In Evita movie, Allan Parker describes women's struggle in the mid of nineteen century as a way to describe women's condition in Argentina strongly dominant in subordinate place. In the movie also view women must brave to take serious risk, in order to reach their right. Furthermore, Allan Parker wants to say that women must have effort to reach equal position in public in the issues of women's position, role, rights, and participation.